(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Hymenopteran parasitoids of Saissetia oleae (Hemipera, Coccidae), 17 other scale insect species nearby (mostly Coccidae), and of insects associated with these scale infestations, were studied at 210 sample localities in southern France for over 20 years. Most of the 47 parasitoids were Chalcidoidea but a few Ceraphronoidea, Ichneumonoidea and Proctotrupoidea were also found. Saissetia oleae was associated with predators and detritivores feeding on honeydew, sooty mould and scale debris. The scale host-plants surveyed were citrus, olive, oleander and maquis vegetation. A table is provided, li sting the parasitoid species found, identities of their hosts and associated host-plants, the host life cycle stages parasitised, the number of parasitoid generations per year, and distribution (which was related to winter cold-hardiness).